DIGITAL LITERACY AND SDGs AWARENESS AMONG COMMUNICATION STUDIES STUDENTS AT IISIP YAPIS BIAK - Irwan, Irwan; Amiruddin, Amiruddin; Nurlin, Nurlin (Gema Kampus IISIP YAPIS Biak, 2026)
Abstract This research investigates digital literacy and understanding of the Sustainable Development Goals (SDGs) among Communication Studies students at IISIP YAPIS Biak. The study seeks to examine the formation of students' digital literacy, their comprehension of issues pertaining to the Sustainable Development Goals (SDGs), and the correlation between their digital experiences and their knowledge of sustainable development. The research utilized a descriptive qualitative methodology. Data were gathered by semi-structured interviews, observation, and documentation, and were subsequently evaluated using data reduction, data display, and conclusion drawing. The results indicate that students generally exhibit sufficient foundational skills in utilizing digital media for academic and communicative objectives. However, their digital literacy is still stronger in technical areas than in critical, ethical, and reflective ones. The research indicated that students' awareness of the SDGs is still evolving and is mostly characterized by a general understanding rather than a comprehensive grasp. Furthermore, students that actively seek information from diverse sources, participate in academic discourse, and monitor societal issues via digital media generally have a heightened understanding of sustainable development. These results show that being digitally literate is a key part of helping pupils understand the SDGs and how they affect society. So, colleges and universities need to improve their students' critical digital literacy and include SDG ideals in their lessons so that they can become responsible, socially aware, and adaptable to technology as future agents of change.